2021
DOI: 10.1111/fcp.12679
|View full text |Cite
|
Sign up to set email alerts
|

The HIV reverse transcriptase Inhibitor Tenofovir suppressed DMH/HFD‐induced colorectal cancer in Wistar rats

Abstract: Colon rectal cancer (CRC) is the second commonest malignancy in developed countries and a significant cause of mortality. Tenofovir reportedly reduces the risk of hepatocellular carcinoma and interferes with cell cycle and cell proliferation. The current study investigated the potential antitumor effect of tenofovir against experimentally induced CRC. CRC was induced by 1,2-dimethylhydrazine (DMH, 20 mg/kg, once a week) and high-fat diet (HFD) in Wistar rats. Rats received tenofovir at a dose of 25 or 50 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…A high-fat diet can lead to obesity, which causes the adipocyte to release more adipokines that cause inflammation [ 20 ]. In this study, the histopathological examination of DMH/HFD rats demonstrated abnormal development in the colon tissue matching with previous findings [ 37 ]. Furthermore, DMH-induced rats with a high-fat diet had a considerably greater number of ACF than DMH-induced rats with a normal-fat diet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A high-fat diet can lead to obesity, which causes the adipocyte to release more adipokines that cause inflammation [ 20 ]. In this study, the histopathological examination of DMH/HFD rats demonstrated abnormal development in the colon tissue matching with previous findings [ 37 ]. Furthermore, DMH-induced rats with a high-fat diet had a considerably greater number of ACF than DMH-induced rats with a normal-fat diet.…”
Section: Discussionsupporting
confidence: 91%
“…The specimen slides were stained with hematoxylin and eosin. The stained specimen slides were covered using slip slides [ 37 ]. The histopathology changes were examined by a pathologist.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it can produce an anti-CRC effect by interfering with the virus. Zidovudine is a nucleoside antiretroviral drug inhibiting CRC cell proliferation ( Fang et al, 2017 ; Sherif et al, 2021 ). Ganciclovir inhibits the NLR family pyrin domain containing 3 activations and reduces the irinotecan-induced intestinal toxicity ( Huang et al, 2020 ).…”
Section: Drug Repurposing and Microbiota In Colorectal Cancermentioning
confidence: 99%
“…Tenofovir also inhibits the activity of human telomerase [119], a crucial enzyme for tumorigenesis and cancer proliferation, whose inhibition represents a promising therapeutic strategy in cancer treatment [120,121]. Sherif et al demonstrated that rats receiving tenofovir at a dose of 50 mg/kg for 24 weeks had diminished colorectal cell proliferation attributed to decreased Bcl-2 and cyclin D1 expression [60]. Zidovudine, also known as azidothymidine, is another nucleoside reverse transcriptase inhibitor (NRTI) used in the treatment of human immunodeficiency virus (HIV) [122].…”
Section: Anti-retroviral Drugsmentioning
confidence: 99%